Necrobiotic Xanthogranuloma in a Patient with Multiple Myeloma - Marlies Wruhs; Robert Feldmann; Isabelle Sawetz; Friedrich Breier; Andreas Steiner (Karger Publishers, 2016)
An 82-year-old woman presented with a 9-month history of multiple, well-defined skin lesions on her neck and upper chest, progressively increasing in size. Histological examination of a skin biopsy showed a regular epidermis. In the dermis, granulomatous changes with central necrobiosis were found which extended focally into the subcutaneous fat. The necrobiotic areas were surrounded by Touton cells and foreign-body giant cells. Laboratory analysis revealed leucopenia. Serum electrophoresis and immunofixation disclosed the presence of an IgG-λ paraprotein. Bone marrow aspiration cytology showed 20% plasmatic cells. The skeletal X-ray revealed frontal and occipital osteolytic skull lesions as well as pubic osteolysis. Urinalysis was unremarkable without proteinuria. Based on the clinical, laboratory, and histological findings, necrobiotic xanthogranuloma in association with multiple myeloma was diagnosed. The patient was treated with bortezomib combined with oral dexamethasone. Follow-up at week 13 revealed the complete disappearance of the IgG paraproteinemia. However, the skin lesions remained unchanged. Therefore, bortezomib treatment was discontinued, and systemic corticosteroids were continued at a higher dosage. After the steroid treatment, the lesions markedly flattened.